Радянське минуле в оцінках студентів-істориків - Гайдай, О.Ю. (Український історичний журнал, 2014)
Аналізується проблема ставлення до радянського минулого за результатами
опитувань, проведених восени 2013 р. у вишах Центральної України – регіоні,
який традиційно відіграє важливу роль у переломні моменти новітньої історії
(парламентські, президентські вибори, Революція гідності). Ставлення до радянського
минулого – надзвичайно важливий елемент формування національної
ідентичності, котрий позначається на політичній орієнтації, соціальній мобільності
та геополітичному виборі населення. Питання про те, як радянське
минуле представлене в «колективній пам’яті» та поглядах поколінь, для яких
це минуле – частина певних соціально-культурних конструктів, а не складова
власного життєвого досвіду, важливе для розуміння політики пам’яті в незалежній Україні. The article investigates the problem of evaluation of the Soviet past using the results
of surveys conducted in autumn 2013 in the universities of Central Ukraine. Usually
in the Ukrainian historiography the politics of memory is been analyzed through the
dichotomy of “East” – “West”. Instead, this article focuses on the region of Central
Ukraine, which plays important role in the crucial moments of modern history. This
tendency has been repeatedly confirmed by the parliamentary and presidential election
results, and during the events of so-called “Revolution of Dignity” become even
more apparent. The attitude to the Soviet past plays extremely important element
in the formation of Ukrainian national identity, as it has impact on the formation
of political orientation, social mobility and geopolitical preferences of population.
Therefore, the question of how the Soviet past is presented in the “collective memory”
of generation who doesn’t have a direct experience of leaving in the USSR, is crucial
for understanding the politics of memory in Ukraine, its achievements, shortcomings
and perspectives.